A Combination of Coconut Fiber Suture and Tamarind Seed Gel with Dehydrated Human Amnion Membrane for Wound Surgery in Rats - Raghu Babu Pothireddy; Angeline Julius; Manu Thomas Mathai; Ganesh Lakshmanan; Beimnet Asfaw Hailemariam (Advances in Materials Science and Engineering)
Today, there are over 2,000 different biomaterials used for various medical applications, but none of these biomaterials are 100% compatible with all human beings. Coconut fiber is widely available but has not been tested as a safe natural alternative for sutures. Immature coconut fiber is nonabsorbable and is effective for cuts and open wounds when used in combination with dehydrated human amnion membrane (dHAM). Immature coconut fiber, tamarind seed polysaccharide (TSP), and dHAM were prepared to test their combinational effect on wound healing in rats. TSP enhanced cell viability, proliferation, and migration in human skin cells and cured wounds both individually and in combination with dHAM. An antibiotic-free combination of the human amniotic membrane with intact epithelium, tamarind seed polysaccharide, and immature coconut fiber provided faster wound healing. Significantly higher wound healing was seen on the 11th day based on an initial 10 mm biopsy punch surgery in Wistar rats compared to control groups. Histological studies revealed thickened dermis edges with more neutrophil infiltration. Collagen deposition in the dermis was homogeneous across the excised skin tissue in the test group, again attesting to the utility of this procedure. This research signifies the use of TSP gel together with the amnion membrane representing a “smart patch” with wound healing potential, which would encourage further research on the smart patch made using a combination of plant and animal biological materials.